The Understanding of Hadith on Jihad in LDII: A Study of Wali Barokah Kediri and Gading Mangu Jombang Pesantrens - Anam, Wahidul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
Abstract: Jihad is a term that continuously caught the attention of academics. The stigma of “radicalism” became a topic of discussion along with the emergence of various religious-based violence in Indonesia. The Indonesian Institute of Islamic Dawah (LDII) pesantrens (Islamic boarding schools) in Jombang and Kediri, East Java, are among large pesantrens in East Java, which have unique characteristics, including the study of the main books of hadi>th, Sahi>h al-Bukha>ri> and Sahi>h Muslim. This article sheds light on their interpretation of hadi>th on jihad and its implication on the development of religious radicalism thoughts in LDII. It suggests that no indication of religious-based violence emerged in both LDII pesantrens. The students have been exposed to religious radicalism and have studied on jihad, but there have been almost no violent or radical movements in performing their religious duties. In addition, the students showed significant radical attitudes towards jihad. They agreed with jihad as written in the hadi>th books and ready to carry out jihad. Abstrak: Jihad merupakan satu istilah konseptual yang terus mendapat perhatian dari para akademisi. Stigma “radikalisme” menjadi topik perbincangan seiring dengan munculnya berbagai kekerasan berbasis agama di Indonesia. Pesantren Lembaga Dakwah Islam Indonesia (LDII) di Jombang dan Kediri, Jawa Timur, termasuk di antara pesantren-pesantren besar di Jawa Timur yang memiliki ciri khas, di antaranya adalah kajian terhadap kitab-kitab hadis otoritatif, yaitu Sahi>h al-Bukha>ri> dan Sahi>h Muslim. Artikel ini menyoroti interpretasi mereka terhadap hadis tentang jihad dan implikasinya terhadap perkembangan pemikiran radikalisme agama di LDII. Tulisan ini menunjukkan bahwa tidak ada indikasi kekerasan berbasis agama yang muncul di kedua pesantren LDII tersebut. Para santri pada dasarnya telah bersinggungan dengan radikalisme agama dan juga telah mempelajari jihad, namun hampir tidak ditemukan adanya gerakan kekerasan atau radikal dalam menjalankan tugas keagamaannya. Meski demikian, di sisi lain para santri juga menunjukkan sikap radikal yang signifikan terhadap jihad. Hal itu tampak dari sikap mereka yang sepakat dengan jihad seperti yang tertulis dalam kitab-kitab hadits dan mereka juga siap untuk melakukan jihad.